Ferment in the Field: Notes on the Evolution of Communication Studies and its Disciplinary Nature - Nordenstreng, Kaarle (Javnost-The Public, 2004)
One of the questions addressed by the colloquium focused on the changing status and character of communication and media studies in universities. This article follows that institutional perspective about communication research in general and critical media studies in particular. First the evolution of the field since the 1950s is reviewed through a number of stages, which coincide with the history of leftist thinking – six ferments, one for each decade. Then the disciplinary nature of the field is discussed, with special reference to the ongoing reform of higher education in Europe known as the “Bologna process.” An illustrative case is provided by a survey of the field in the Scandinavian countries. The conclusion is that there is a need for radical reflection about the discipline in the contemporary world, calling for an approach to media studies in terms of the philosophy of science. The article presents notes for further thought rather than suggests final scenarios, and this is done from an admittedly personal and national perspective – as a veteran of the field and as a member of the Finnish community.